Saliva and its role in the transmission of covid-19 - what the dentist needs to know - Rafael Santiago, Ibeth Stefani (2021)
The use of mesenchymal stem cells for bone regeneration in the oral cavity due to its differentiation capacity is part of the most promising scientific advances in regenerative medicine. The knowledge about this cell therapy obtained in recent times has been raising the expectations of health professionals; however there is still much to discover. The objective was to analyze the current evidence on the use of stem cells for guided bone regeneration in the dental field, through the bibliographic search of 30 indexed publications in Spanish and English registered from 2010 to 2020 in the databases: scielo , pubmed and academic google. The results demonstrated its effectiveness in planned bone regeneration in specialties such as periodontics and maxillofacial surgery; however, more research and the search for solutions are still required to facilitate its obtaining, maintenance and cultivation. In addition, it is necessary to know its indications and contraindications for a successful treatment.